If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 + -7x = 9x + -55 Reorder the terms: 41 + -7x = -55 + 9x Solving 41 + -7x = -55 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 41 + -7x + -9x = -55 + 9x + -9x Combine like terms: -7x + -9x = -16x 41 + -16x = -55 + 9x + -9x Combine like terms: 9x + -9x = 0 41 + -16x = -55 + 0 41 + -16x = -55 Add '-41' to each side of the equation. 41 + -41 + -16x = -55 + -41 Combine like terms: 41 + -41 = 0 0 + -16x = -55 + -41 -16x = -55 + -41 Combine like terms: -55 + -41 = -96 -16x = -96 Divide each side by '-16'. x = 6 Simplifying x = 6
| -2(3-y)+8-5(2y-1)=3y | | 3+5x=8+4x | | 3d+4=2+3d-.5 | | 23x-52-17x=80-6x-12 | | -4(2w-5)=3w-13 | | 4.5x+3.4=1.5x-2.6 | | 8(3+n)-2(6n+5)= | | -x(7x-1)+8(1+8)= | | x-1=2-2x | | -3(r-5)+5(-5+4r)= | | 6(q-5)-19=5 | | -4+13x=3x+-8(2+x) | | -4m(6+m)+2m(4m+2)= | | 4n+24=2c+6 | | -5(7n-8)-7n(n-4)= | | 11w+2(w+1)=5x-6 | | 2(2m+5)=3m-5 | | -6(5p+6)+7(p+5)= | | -(v+4)+3= | | -5(3-x)+x= | | 15-3x=-6 | | 100t=10+70t | | 9x+4=8x-6 | | 5(-2-2x)-3= | | 6x-(4-7x)= | | 3(-7-3x)+x= | | -2n-3(5n-1)= | | 8-2(k-6)= | | c=b-bx | | 106+4n=58 | | -2(1-2a)-2= | | 4b-2b= |